(untitled) (Research, Society and Development, 2020)
By using Rogers’s theory (1983), this research aims to know the process of adopting innovation occurred in the Telkomsel customers toward Line Chatterbot Mobile Messenger. Another purpose of this research is tried to find out the differences of adoption process from generation X, millennial, and generation Z as well as describe each of the adopter category characteristics. The method used is case study with qualitative approach using Focus Group Discussion technique. The results then reveal that the adoption process has little bit differences with Rogers’s theory. The differences are found in several steps including knowledge steps, experiment steps, decision steps, and confirmation steps. Furthermore, this research is also found out new concepts namely passive adopter which is defined as adopter that prefers using innovation as alternative choices.